2012
DOI: 10.1016/j.ydbio.2011.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Cell autonomy of DSCAM function in retinal development

Abstract: Cell adhesion molecules (CAMs) provide identifying cues by which neural architecture is sculpted. The Down Syndrome Cell Adhesion Molecule (DSCAM) is required for many neurodevelopmental processes in different species and also has several potential mechanisms of activity, including homophilic adhesion, homophilic repulsion and heterophilic interactions. In the mouse retina, Dscam is expressed in many, but not all neuronal subtypes. Mutations in Dscam cause the fasciculation of dendrites of neighboring homotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 49 publications
4
41
0
Order By: Relevance
“…Defects in horizontal-cell dendritic process self-avoidance in PlexA4 -/- and Sema6A -/- retinas result in abnormal dendrite elaboration, and these phenotypes likely affect the formation of appropriate connections with neighboring horizontal cell dendrites and/or cone photoreceptor axon terminals. The horizontal-cell self-avoidance defect we observe is unique in that it is not accompanied by alterations in horizontal-cell mosaic cell body spacing, as is observed in DSCAMs mutants (Fuerst et al, 2008; Fuerst et al, 2009; Fuerst et al, 2011). …”
Section: Discussionsupporting
confidence: 53%
“…Defects in horizontal-cell dendritic process self-avoidance in PlexA4 -/- and Sema6A -/- retinas result in abnormal dendrite elaboration, and these phenotypes likely affect the formation of appropriate connections with neighboring horizontal cell dendrites and/or cone photoreceptor axon terminals. The horizontal-cell self-avoidance defect we observe is unique in that it is not accompanied by alterations in horizontal-cell mosaic cell body spacing, as is observed in DSCAMs mutants (Fuerst et al, 2008; Fuerst et al, 2009; Fuerst et al, 2011). …”
Section: Discussionsupporting
confidence: 53%
“…This suggested that mouse Dscams are acting as part of a larger identity code, and do not specify cell type [13]. Conditional deletion of Dscam confirmed that the protein acts to prevent fasciculation by acting within and not between retinal cell types and through homotypic binding, in that the null phenotype is dominant within cell types, that is mutant cells will entangle homotypic wild type cells within the same retina [34]. All of these mechanisms in mouse retina are consistent with DSCAM acting as a homophilic transmembrane cell adhesion molecule.…”
Section: Discussionmentioning
confidence: 98%
“…Dscam del17 , Dscam 2J , Dscam F and Dscam FD mice (truncation, protein null, conditional and germ line-targeted conditional, respectively) were genotyped as previously described (Fuerst et al, 2012; Fuerst et al, 2010; Fuerst et al, 2008). Dscam del17 , Dscam 2J and Dscam FD mice are collectively referred to as Dscam LOF (loss of function) unless otherwise noted.…”
Section: Methodsmentioning
confidence: 99%